Hydrogen induced contact resistance - Hamer, P (University of Oxford, 2018)
The data contains matlab workspaces and origin project files for the publication entitled "Hydrogen Induced Contact Resistance in PERC Solar Cells". In the matlab files the following variables are given: H1: H+ at each point H2: H0 at each point H3: H- at each point Ht: Total interstitial hydrogen Hphos: [HP] Hboron: [HB] electrons holes Efield: Electric field in V/cm time for each row in other parameters diff1: diffusion of H+ at each point diff2: diffusion of H0 at each point diff3: diffusion of H- at each point drift1: drift of H+ at each point drift3: dift of H- at each point